Pengaruh Fraud Triangle terhadap Kecenderungan Fraud Anggaran Dana Desa dan Budaya Organisasi sebagai Variabel Moderasi: (Studi pada Pemerintah Desa di Kabupaten Sikka) - Elisabeth Yessi Da Rato; Lilis Ardini; Kurnia (Owner : Riset dan Jurnal Akuntansi, 2023)
This research aimed to examine and analyze the effect of the fraud triangle which was referred to as pressure, opportunity, and rationalization on the fraud tendency of village funds budget, and organizational culture as moderating variable. The research was qualitative. Moreover, the data collection technique used purposive sampling which the sample was based on the criteria given. In line with that, there were 60 samples from 147 villages in the Sikka district with a total of 240 respondents. Furthermore, the instrument in the sampling technique used the Slovin formula. Additionally, the data analysis technique used multiple linear regression with Moderated Regression Analysis (MSA) test. As the result, it showed that: 1) pressure had a positive effect on the fraud tendency of the village funds budget, 2) opportunity had a positive effect on the fraud tendency of the village funds budget, 3) rationalization had a positive effect on the fraud tendency of the village funds budget, 4) organizational culture had a negative effect on fraud tendency of village funds budget, 5) organizational culture did not moderate the effect of pressure on the fraud tendency of village funds budget, 6) organizational culture did not moderate the effect of opportunity on the fraud tendency of village funds budget, 7) organizational culture did not moderate the effect of rationalization on the fraud tendency of village funds budget.